Right-wing Christian Intervention in a Naïve Polity. Issue 2 (1st March 2014) - Maddox, Marion
Abstract The Australian Christian Lobby (ACL), which established itself in the national capital in 1995 as a registered company limited by guarantee, declares itself "rigorously non-partisan, " enjoying "credibility with church leaders, political parties and the media, " and making "a real difference on issues of concern to Christians." From its base in Eternity House, Canberra, the ACL has been credited with some remarkable achievements, including persuading an atheist prime minister, herself living in an unconventional relationship, to maintain her seemingly incongruous opposition to marriage equality for same-sex couples. This article argues that the ACL has achieved its influential position by successfully presenting itself as politically, theologically, and culturally middle-of-the-road. The article analyses the ACL's claims about itself, the campaigns it conducts and the international networks to which its founders and board members relate in the light of political science theories of right-wing extremism. It finds that some ACL positions meet at least some formal definitions of right-wing extremism. This analysis further suggests that the category of "extreme right" offers both greater subtlety and more utility for study of the Christian right than some of its scholars have proposed.